EFFECTS OF NUCLEAR FACTOR OF ACTIVATED T-CELLS 5 (NFAT5) KNOCKOUT IN RENAL TUBULAR CELLS ON RENAL FIBROGENESISNFAT5 (NUCLEAR FACTOR OF ACTIVATED T-CELLS 5) IS A TRANSCRIPTION FACTOR. (April 2021) - Izumi, Yuichiro; Ono, Makoto; Eguchi, Koji; Matsuo, Naomi; Hiramatsu, Akiko; Nakayama, Yushi; Inou, Hideki; Kakizoe, Yutaka; Kuwabara, Takashige; Mukoyama, Masashi
Abstract : Objective: NFAT5 (nuclear factor of activated T-cells 5) is a transcription factor that stimulates the expression of osmoprotective genes in response to extracellular hypertonicity, contributing to cell survival even in extreme hypertonic conditions as seen in renal medulla. Recent studies have suggested that activation of NFAT5 in macrophages in the skin induces lymphangiogenesis in response to high-salt diet, alleviating salt-sensitive hypertension. Pathophysiological roles of NFAT5 in the kidney, however, are still obscure. Not only hypertonicity but also hypoxia, oxidative stress, and toll-like receptor signaling, which promote fibrogenesis in the kidney, have been suggested to increase the NFAT5 activity. In the present study, the role of NFAT5 in renal fibrogenesis was examined using renal tubular cell-specific NFAT5 conditional knockout mice. Design and method: We generated renal tubular cell-specific NFAT5 conditional knockout (cKO) mice by crossing NFAT5 floxed mice with Pax8-rtTA/LC-1 mice, in which Cre recombinase was specifically expressed in renal tubular cells by the treatment with doxycycline. Wild-type (WT) mice and NFAT5 cKO mice were subjected to unilateral ureteral obstruction (UUO) or sham-operation. After 7 days, mice were sacrificed and kidneys were removed. The mRNA expression levels of NFAT5 and markers for fibrogenesis (TGF-beta, alfa-SMA, CCL2, Col1, Col3, KIM-1, and NGAL) in the kidney were examined by real-time PCR. Renal fibrosis was evaluated by Azan staining. Results: In WT mice, the expression of NFAT5 mRNA was two times greater in the kidney from UUO mice than that from sham-operated mice. Expressions of fibrogenesis-related genes were significantly increased in the kidney from UUO mice compared with those from sham-operated mice. In the UUO groups, the expressions of fibrogenesis-related mRNAs were significantly higher in the kidney from NFAT5 cKO mice compared with those from WT mice. Azan staining showed that UUO-induced renal fibrosis tended to get worse in NFAT5 cKO mice compared to WT mice. Conclusions: NFAT5 in renal tubular cells may exert protective actions against the development of renal fibrosis caused by UUO.